Systematic Literature Review: 21st-Century English Learning Media Utilizing Augmented Reality - Trisnawati, Winda; Sulistiyo, Urip; Sofyan, Sofyan; Haryanto, Eddy; Bashir, Ashadi (Vocational: Journal of Educational Technology, 2025)
The rapid advancement of technology has significantly impacted education, particularly in the field of language learning. Among the most promising innovations is Augmented Reality (AR), a technology that enhances the real world with digital content, creating immersive and interactive learning experiences. This potential for immersion allows AR to engage students effectively, making it a powerful tool in supporting 21st-century learning skills such as critical thinking, creativity, collaboration, and communication. This systematic literature review aims to analyze the current body of research on AR in English language education, focusing on its ability to enhance language proficiency, retention, and fluency, while also fostering key 21st-century skills. By examining the benefits, challenges, and gaps in the literature, this review provides valuable insights for educators, researchers, and policymakers interested in incorporating AR into language education to improve learning outcomes.